Current videofluoroscopy practice in the United Kingdom: A survey of imaging professionals. Issue 2 (May 2021) - Boaden, E.; Nightingale, J.; Hives, L.; Bradbury, C.; Benfield, J.; Patel, T.; Georgiou, R.
Abstract: Introduction: Videofluoroscopy (VFSS) is a frequently used radiological investigation for dysphagia and is conducted within a radiology setting by speech and language therapists (SLTs) working alongside imaging personnel (radiologists and/or radiographers). Previous surveys of SLT practice have reported variability in VFSS protocols and procedures. The aim of this study was to explore current clinical practice for VFSS from the perspective of imaging personnel engaged in VFSS within the United Kingdom. Methods: A comprehensive online survey enabled exploration of current practices of imaging professionals. Target participants were diagnostic imaging personnel (radiographers and radiologists) with experience of working in VFSS clinics. Descriptive statistics describe and summarise the data alongside inferential statistics where appropriate. Results: 54 survey participants represented 40 unique acute healthcare organisations in the UK, in addition to two respondents from the Republic of Ireland. The survey demonstrated high variance in clinical practice across all stages of the VFSS procedure. Clinicians were not always compliant with current UK guidelines and the roles and responsibilities of different professionals working within the clinics were often not clearly defined. Conclusion: Further research is required to develop new international, interprofessional VFSS guidelines to standardise service delivery for VFSS, improving diagnostic accuracy, efficiency and patient experience. Implications for practice: In the absence of VFSS guidelines for imaging personnel, practitioners should familiarise themselves with the UK Royal College of Speech and Language Therapists VFSS Position paper; IR (ME)R guidelines and DRLs for the client groups with which they work to guide clinics and improve practice. Clinicians should revisit protocols and clinical governance regarding safe practice in order to improve the quality of care within the VFSS clinic.